Mechanisms of Smooth Muscle Cell Differentiation Are Distinctly Altered in Thoracic Aortic Aneurysms Associated with Bicuspid or Tricuspid Aortic Valves - Ignatieva, Elena; Kostina, Daria; Irtyuga, Olga; Uspensky, Vladimir; Golovkin, Alexey; Gavriliuk, Natalia; Moiseeva, Olga; Kostareva, Anna; Malashicheva, Anna (Frontiers in Physiology, 2017)
Cellular and molecular mechanisms of thoracic aortic aneurysm are not clear and therapeutic approaches are mostly absent. Thoracic aortic aneurysm is associated with defective differentiation of smooth muscle cells (SMC) of aortic wall. Bicuspid aortic valve (BAV) comparing to tricuspid aortic valve (TAV) significantly predisposes to a risk of thoracic aortic aneurysms. It has been suggested recently that BAV-associated aortopathies represent a separate pathology comparing to TAV-associated dilations. The only proven candidate gene that has been associated with BAV remains NOTCH1. In this study we tested the hypothesis that Notch-dependent and related TGF-β and BMP differentiation pathways are differently altered in aortic SMC of BAV- versus TAV-associated aortic aneurysms. SMC were isolated from aortic tissues of the patients with BAV- or TAV-associated aortic aneurysms and from healthy donors used as controls. Gene expression was verified by qPCR and Western blotting. For TGF-β induced differentiation SMC were treated with the medium containing TGF-β1. To induce proosteogenic signaling we cultured SMC in the presence of specific osteogenic factors. Notch-dependent differentiation was induced via lentiviral transduction of SMC with activated Notch1 domain. MYOCD expression, a master gene of SMC differentiation, was down regulated in SMC of both BAV and TAV patients. Discriminant analysis of gene expression patterns included a set of contractile genes specific for SMC, Notch-related genes and proosteogenic genes and revealed that control cells form a separate cluster from both BAV and TAV group, while BAV- and TAV-derived SMC are partially distinct with some overlapping. In differentiation experiments TGF-β caused similar patterns of target gene expression for BAV- and TAV derived cells while the induction was higher in the diseased cells than in control ones. Osteogenic induction caused significant change in RUNX2 expression exclusively in BAV group. Notch activation induced significant ACTA2 expression also exclusively in BAV group. We show that Notch acts synergistically with proosteogenic factors to induce ACTA2 transcription and osteogenic differentiation. In conclusion we have found differences in responsiveness of SMC to Notch and to proosteogenic induction between BAV- and TAV-associated aortic aneurysms.